Strategi Pemasaran Pariwisata Tiga Nusa Terhadap Peningkatan Pengunjung Melalui E-Commerce - Ni Putu Eka Kurnia Dewi (Universitas Pendidikan Nasional, 2018)
This study concerning with the tourism marketing strategy of Three Nusa (Nusa Penida, Nusa Lembongan and Nusa Ceningan Island in Bali) to increase visitor through e-commerce especially using website and social media. The aim of present study was to know tourism marketing strategy of Three Nusa through e-commerce especially using website and social media to increase the number of tourists visit. This paper uses qualitative technique with observation, interview and document study to collect data. Data analysis was carried out though data reduction, data display and conclusion and verification. The result suggest that most of the tourism companies in Three Nusa use e-commerce especially website and social media as promotional and marketing tools to attract tourist to visit those tourism object. They argued that tourism marketing strategy using e-commerce especially website and social media was more effective than conventional and traditional marketing or promotion. In implementing tourism marketing strategy using e-commerce especially website and social media to increase tourists visit, tourism companies in Three Nusa also try to implement online marketing mix. Those strategies cover product, price, place, promotion, people, process and physical evidence